Multidisciplinary solutions supported by digitized tools based on eco-humanistic model - Glazar, Tadej; Sergeyeva, Tetyana; Kushchenko, Zhanna (My University, 2023)
The research presents an innovative approach to creating digitized tools for multidisciplinary and multi-actor solutions aimed at after-war/disaster recovery and development of affordable housing districts based on eco-humanistic model within New European Bauhaus coordinates. It is proposed innovative approach and instruments for digital support of synergetic solutions based on modelling experts, users and stakeholders’ optimal actions with consideration of their cognitive schemes diversity and orientated to ultimate goal. The model is realized as demonstrator for replication.
Keywords: pedagogical activity; digital technologies; education; eco-humanistic model